Potential impact of Thai Kidney Transplant program on immunosuppressive utilization: An analysis of the national transplant registry - K. Pongpirul (2018)
Background The Thai Kidney Transplant (TKT) program was launched in October 2008 to promote transplantation among previously disadvantaged populations, using fixed-rate provider payment. This study investigated if the introduction of this program could alter the natural practice trends of immunosuppressive drug use. Methods Data from the Thai Transplantation Registry were analyzed. The change in trend of immunosuppressive use was assessed using the multivariate adaptive regression splines (MARS) technique. Results During 1987-2012, 3975 kidney transplantations were done. The average age of patients was 42 years and 62% were male. Chronic glomerulonephritis accounted for one third of those with known causes of end-stage renal disease (ESRD). Eighty-six percent were on hemodialysis before transplantation. Prednisolone was used in 95.87% of all transplant recipients, whereas calcineurin inhibitors (CNIs), mycophenolates (MPAs), azathioprine (AZA), and mammalian target of rapamycin inhibitors (mTORis) were used in 95.67%, 64.22%, 12.25%, and 2.31%, respectively. Overall use after 2008 was decreased for AZA (18.16% to 3.40%) and mTORis (2.86% to 1.5%) but increased for MPAs (50.80% to 84.34%), CNIs (95.43% to 96.04%), and prednisolone (95.60% to 96.29%), as compared with before the program inception. The slopes of use trends of AZA, MPAs, and CNIs did not significantly marginally differ from their natural trends before the program inception (P =.496,.108, and.741, respectively). However, the natural increasing use trend of mTORis significantly changed to a decreasing pattern after the introduction of the TKT program (P =.018). Conclusion Fixed-rate provider payment might interfere with the natural practice trends of immunosuppressive drug use. © 2014 by Elsevier Inc. All rights reserved.